Peran Agama Terhadap Pengaruh Kesehatan Mental pada Mahasiswa: Studi Kasus Universitas Muhammadiyah Surakarta - Sovia Dewi Maulita; Veri Dwi Adiningsih; Lusiana Noviawati; Alif Galuh Ristika; Briliana Fian Hartanti; Diana Nur Apni; Ahmad Nurrohim (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Mental health issues are still a hot topic being discussed amidst a generation flooded with vast amounts of information. The information that arises correlates with the impact felt by various groups, including the general public, students, and university students. Positive information that is informative or other information that is trivial can influence how someone behaves. The tendency for students to experience excessive anxiety, commonly referred to as overthinking, stems from their habit of scrolling through and comparing themselves with the achievements of others on social media. This is one of the disorders that contributes to the mental health issues caused by frequent consumption of social media. A lack of religious knowledge plays a significant role in how individuals process information. The awareness of the importance of religious knowledge needs to be instilled in every educated student so that their academic pursuits do not overshadow their obligations as servants of Allah, who are still given the opportunity to accumulate good deeds. This research employed a qualitative approach over four days using a Google Form survey as the questionnaire tool. The purpose of this research is to process the data obtained to provide clear facts from the field.